The role of Arab Open University in developing its graduates’ economic and social returns - Harith Abood Abbas; Abeer Deranieh (Intelektual Pustaka Media Utama, 2019)
This study aimed at finding out the economic and social returns achieved by Arab Open University graduates of 2012-2014. The sample consisted of 251 out of 1565 BA male and female graduates who voluntarily identified the sort of returns they achieved by choosing any of 43 items included in a questionnaire posted on their emails, put on the University’s site and distributed at the Alumni Club meeting in 2017. The researchers used means, standard deviations and percentages to identify the economic and social returns gained by the graduates, while they used (T Test) to find differences in these returns due to gender and (One Way ANOVA) to know the differences in these returns due to the adequacy of the academic programs. The results showed a wide range of economic and social returns achieved by the graduates, as a result of the open learning style in the University, while no significant differences were noticed in these returns due to gender or specialization.